Defining Formats and Corpusbased Examples in the General Ndebele Dictionary, Isichazamazwi SesiNdebele * - Langa Khumalo (Lexikos, 2011)
Abstract: In this article the writer evaluates the defining formats that were used in defining headwords in the first monolingual General Ndebele Dictionary, Isichazamazwi SesiNdebele (ISN). The emphasis in the ISN was on the concept of user-friendliness. The article establishes that defining formats in the ISN are a judicious mixture mainly of the defining formats of the Collins Birmingham University International Language Database (COBUILD) and of what has been referred to as traditional formats. The first part of this article is an analysis of the decisions taken by the ISN editors in formulating their defining formats. It assesses the COBUILD defining principle vis-?-vis its application in defining headwords in the ISN and the impact of this principle on the userfriendliness of the dictionary. It further discusses other formats, including the decision to retain traditional defining formats for defining headwords. One of the traditional defining styles agreed upon was that the editors were to give the hypernym in the case of semantic sets, and then to identify the concept being defined by specifying aspects that distinguish it from others of its type. The second part of the article evaluates the importance and use of the corpus in providing both definitions and examples for the ISN. However, it is further argued that since a corpus has to be "representative" in terms of size in order to be appropriately used as basis for such corpus-based dictionaries, the ISN editors whose corpus was relatively small, could not avoid relying on intuitive knowledge in constructing some examples. Keywords: COBUILD, CORPUS, DEFINITION, DEFINING FORMATS, TRADITIONAL FORMATS, EXAMPLES, USER-FRIENDLINESS, COTEXT, CONCORDANCE. Opsomming: Definieerpatrone en korpusgebaseerde voorbeelde in die AlgemeneNdebelewoordeboek, Isichazamazwi SeSiNdeble. In hierdie artikel beoordeeldie skrywer die definieerpatrone wat in die eentalige Algemene Ndebelewoordeboek, IsichazamazwiSesiNdebele (ISN) gebruik is. Die klem in die ISN was op die konsep gebruikersvriendelikheid.Die artikel toon aan dat definieerpatrone in die ISN 'n oordeelkundige mengsel is hoofsaaklikvan die definieerpatrone van die Collins Birmingham University International Language Database (COBUILD) en van waarna verwys word as tradisionele patrone. Die eerste deel van hierdie artikelis 'n ontleding van die besluite geneem deur die redakteurs van die ISN by die formulering van huldefinieerpatrone. Dit beoordeel die definieerbeginsel van COBUILD ten opsigte van die aanwendingdaarvan by die definiëring van trefwoorde in die ISN en die uitwerking van hierdie beginselop die gebruikersvriendelikheid van die woordeboek. Verder bespreek dit ander patrone, inbegrepedie besluit om tradisionele definieerpatrone te behou vir die omskrywing van trefwoorde. Eenvan die tradisionele definieerstyle waaroor ooreengekom is, was dat die redakteurs die hiperniemsou gee in die geval van semantiese stelle, en dan die konsep wat gedefineer word, te identifiseerdeur die spesifisering van aspekte wat dit onderskei van ander van sy soort. Die tweede deel vandie artikel beoordeel die belangrikheid en gebruik van die korpus in die verskaffing van soweldefinisies as voorbeelde vir die ISN. Daar word egter verder geredeneer dat, aangesien 'n korpus"verteenwoordigend" moet wees in terme van grootte ten einde toepaslik gebruik te word as basisvir sulke korpusgebaseerde woordeboeke, die redakteurs van die ISN wie se korpus relatief kleinwas, nie kon vermy om op intuïtiewe kennis te steun by die maak van sommige voorbeelde nie. Sleutelwoorde: COBUILD, KORPUS, DEFINISIE, DEFINIEERPATRONE, TRADISIONELE PATRONE, VOORBEELDE, GEBRUIKERSVRIENDELIKHEID, KOTEKS, KONKORDANSIE